Islamic Education and Muslim Revival Indonesian Association of Muslim Intellectuals - Udin, Udin; Sopian, Raden Mas; Andari, An An; Setiawan, Andi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This qualitative study tells the emergence of ICMI as a new political force in Indonesian politics cannot be divorced from its advantages and disadvantages. In moderation, pro circles believe that the emergence of ICMI is, on the one hand, a strategy for the government with its interests, but on the other hand, Muslims can benefit from it. Meanwhile, those who oppose ICMI argue that if it becomes too close to the bureaucracy, it will exacerbate the symptoms of exclusivism and elitism and may even damage the roots of Islamic culture that have been painstakingly built thus far. Furthermore, ICMI was criticized as a tool for election success, allowing Suharto to be re-elected President. ABRI, which played an important political role from the beginning of independence until the New Order, appears to have responded to the rise of Islamic groups, particularly with regard to the birth of ICMI.